RhoGEF2 and the formin Dia control the formation of the furrow canal by directed actin assembly during Drosophila cellularisation. - Großhans, J.; Wenzl, C.; Herz, H.M.; Bartoszewski, S.; Schnorrer, F.; Vogt, N.; Schwarz, H.; Muller, H.A. (Development, 2005)
The physical interaction of the plasma membrane with the associated cortical cytoskeleton is important in many morphogenetic processes during development. At the end of the syncytial blastoderm of Drosophila the plasma membrane begins to fold in and forms the furrow canals in a regular hexagonal pattern. Every furrow canal leads the invagination of membrane between adjacent nuclei. Concomitantly with furrow canal formation, actin filaments are assembled at the furrow canal. It is not known how the regular pattern of membrane invagination and the morphology of the furrow canal is determined and whether actin filaments are important for furrow canal formation. We show that both the guanyl-nucleotide exchange factor RhoGEF2 and the formin Diaphanous (Dia) are required for furrow canal formation. In embryos from RhoGEF2 or dia germline clones, furrow canals do not form at all or are considerably enlarged and contain cytoplasmic blebs. Both Dia and RhoGEF2 proteins are localised at the invagination site prior to formation of the furrow canal. Whereas they localise independently of F-actin, Dia localisation requires RhoGEF2. The amount of F-actin at the furrow canal is reduced in dia and RhoGEF2 mutants, suggesting that RhoGEF2 and Dia are necessary for the correct assembly of actin filaments at the forming furrow canal. Biochemical analysis shows that Rho1 interacts with both RhoGEF2 and Dia, and that Dia nucleates actin filaments. Our results support a model in which RhoGEF2 and dia control position, shape and stability of the forming furrow canal by spatially restricted assembly of actin filaments required for the proper infolding of the plasma membrane.